PENGARUH E-COMMERCE DAN TRANSPORTASI ONLINE TERHADAP HARGA JUAL PRODUK CV. SURYA SAKTI ENGINEERING - Pesta Gultom; Jack Karnadi (Jurnal Manajemen Bisnis Eka Prasetya, 2019)
This study aimed to determine the influence of E-Commerce on selling price of CV. Surya Sakti Engineering’s products, to determine the influence of Online Transportation on selling price of CV. Surya Sakti Engineering’s products, to determine the influence of E-Commerce and Online Transportation on selling price of CV. Surya Sakti Engineering’s products. The research methodology used is quantitative descriptive method. Quantitative data is used in this study, which is obtained in number forms. Data sources are primary and secondary data. Primary data is obtained from questionnaire distribution to customers / business partners of CV. Surya Sakti Engineering. Secondary data is obtained from data and literature which have relationship with this study The population in this study is customers / business partners of CV. Surya Sakti Engineering with the total of 60 respondents. Using saturation sampling method, the sample total is equal to population sample. Data is analyzed by using multiple linear regression analysis method. Results of the analysis show that E-Commerce does not have significant effect on selling price of CV. Surya Sakti Engineering’s products based on partial test result hypothesis. Results of the analysis show Online Transportation does not have significant effect on selling price of CV. Surya Sakti Engineering’s products based on partial test result hypothesis. Results of the analysis show that E-Commerce and Online Transportation does not have significant effect on selling price of CV. Surya Sakti Engineering’s products based on simultaneously test result hypothesis. This study hypothesis result according to coefficient determination apparently shows that there is 3,3% where Selling Price is affected by E-Commerce and Online Transportation. This result therefore shows that Selling Price is affected by unanalyzed variables such as TV advertising, pop-up advertising, competitors, dan more other variables approximately 96,7%.